Rumah Ramah Remaja Sebagai Strategi Penangganan Narkoba dan Pergaulan bebas di Perbatasan Papua dan Papua Nugini - Reni Shintasari; Marlina Flassy; Ferinandus Snanfi; Christine Olidita Sanggenafa; Diego De Fretes (KUAT : Keuangan Umum dan Akuntansi Terapan, 2022)
The purpose of this community service activity is to provide education and knowledge about youth-friendly homes as a place to vent, discuss and consult counseling about children. This service is one form of drug control and promiscuity on the border of Papua and Papua New Guinea. While the partners in this Community Service are teenagers in Central Koya (an area adjacent to the Border) with sufficient knowledge, so participants can gain knowledge and information about the dangers of drugs and drug handling for teenagers. In achieving the goals of this community service program, the service team provided socialization and counseling in one of the houses of the residents of Central Koya, Muaratami, Jayapura City. The expected output target is to become a youth-friendly house as a model for dealing with drug problems and promiscuity in Jayapura City, Papua.